Heat-activated persulfate oxidation of methyl- and ethyl-parabens: Effect, kinetics, and mechanism. (February 2017) - Chen, Yiqun; Deng, Pinya; Xie, Pengchao; Shang, Ran; Wang, Zongping; Wang, Songlin
Abstract: We evaluated the degradation of methylparaben (MeP) and ethylparaben (EtP), two representative parabens, using the heat-activated persulfate system in a laboratory. Both sulfate and hydroxyl radicals contributed to the removal of the two parabens. The degradations of both MeP and EtP were improved by increasing the heating temperature or persulfate dose in accordance with a pseudo-first-order reaction model. The oxidation efficiency of parabens was found to be pH-dependent; decreasing in the order pH 5.0 > 7.0 > 9.0. The presence of chloride, bicarbonate, or humic acid was found to inhibit the degradation of the two parabens to some extent because of competition for the reactive radicals, with humic acid having the most serious effect. Dealkylation of the methyl unit, decarboxylation of the carboxylic group, and subsequent hydrolysis are proposed to be involved in the degradation pathway of MeP. The results suggest that the heat-activated persulfate system might be efficiently applied in the treatment of paraben-containing water samples. This was also supported by the results of applying this system to treat a real water sample containing both MeP and EtP. Highlights: Heat-activated persulfate was firstly applied on parabens oxidation. Both sulfate and hydroxyl radicals contributed to the degradation. Humic acid significantly inhibited the parabens removal. A pathway involved dealkylation, decarboxylation and hydrolysis was proposed.